Analysis and Optimization of Meshing Characteristic of Planetary Gear Train Considering Structure Flexibility - Guangze Zheng; Ya Mei; Jincai Yang (Jixie chuandong, 2021)
Taking the planetary gear train of an AT transmission as the research object， the finite element method is used to analyze the dynamic characteristics of the planet carrier， ring gear and housing， and the accuracy of the finite element model of the housing is verified by combining with the modal experiment. The dynamics analysis model of the AT planetary gear system is established and the contact spot experiment is carried out. Through the comparative analysis of the simulation and experimental contact spot results， it is concluded that the meshing spots of the small sun gear-short planet gear and the long planet gear-ring gear pair are basically the same and there is a significant partial load phenomenon. The dynamics model of the AT transmission is obtained by importing the finite element model of the flexible planet carrier， ring gear and housing， and the transmission characteristics of the planet carrier， ring gear and housing flexibility to the planet gears， and the amount of meshing misalignment parameters are analyzed. The results show that the flexible deformation of the casing and the ring gear has the most significant effects on gear misalignment and transmission errors， followed by the planetary carrier flexibility. By improving the support bearing stiffness， bearing preload and gear parameter optimization methods， the planetary gear train gear meshing characteristics are improved， the planetary gear train gear strength and the AT transmission NVH performance are optimized.